2019
DOI: 10.1186/s13089-019-0131-x
|View full text |Cite
|
Sign up to set email alerts
|

Interscalene brachial plexus nerve block in the emergency department: an effective and practice-changing workshop

Abstract: Background The interscalene brachial plexus nerve block (ISNB) is a potentially useful method of regional analgesia for humerus fracture and shoulder dislocation reduction in the Emergency Department (ED). We examined the effectiveness of an ISNB workshop given to emergency medicine (EM) residents. We also explored complication rates and effectiveness of ISNBs performed in the ED. Methods One-hour evidence-based ISNB workshops were conducted with EM residents. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…It was not reported if this was because they were old and at high risk for drugs use or because of ED overcrowding. A previous study showed that landmark‐guided shoulder joint injections were misplaced in 41.1% of cases by EPs [ 18 ]; the success rate of the interscalene brachial plexus nerve block by EPs was 71% [ 19 ]; shoulder dislocation reduction required a moderate depth of sedation [ 20 ]. Our study did not record pain score and sedation depth, although the 15 patients who used sedatives or analgesics may have had inadequate pain relief or sedation.…”
Section: Discussionmentioning
confidence: 99%
“…It was not reported if this was because they were old and at high risk for drugs use or because of ED overcrowding. A previous study showed that landmark‐guided shoulder joint injections were misplaced in 41.1% of cases by EPs [ 18 ]; the success rate of the interscalene brachial plexus nerve block by EPs was 71% [ 19 ]; shoulder dislocation reduction required a moderate depth of sedation [ 20 ]. Our study did not record pain score and sedation depth, although the 15 patients who used sedatives or analgesics may have had inadequate pain relief or sedation.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple studies examining various methods of teaching UGRA to EPs [36,[75][76][77]. Beals et al conducted a feasibility study to assess if IBPBs could be effectively taught to EM residents through a 1-h workshop [36].…”
Section: Regional Anesthesia Curriculums and Teaching Methodsmentioning
confidence: 99%
“…There are multiple studies examining various methods of teaching UGRA to EPs [36,[75][76][77]. Beals et al conducted a feasibility study to assess if IBPBs could be effectively taught to EM residents through a 1-h workshop [36]. Postworkshop, 93% of participants passed an image acquisition assessment, and 100% passed needle placement assessments, with pass rates 3 months post-workshop being 76% and 100%, respectively [36].…”
Section: Regional Anesthesia Curriculums and Teaching Methodsmentioning
confidence: 99%
See 2 more Smart Citations